Evaluation of exogenous application of polyamines on callus growth of mangaba tree (Hancornia speciosa Gomes) - Fráguas, Chrystiane Borges [UNESP] (2009)
The effect of polyamines spermine and spermidine in the calluses growth of Hancornia speciosa Gomes was studied. Calluses with 0.5 cm diameter were inoculated in Murashige & Skoog (1962) (MS) medium 50% + hidrolizated casein 100 mg L-1 + yeast 200 mg L-1, according to the treatments: A: spermine 1 mmol + 2.4-D 2 mg L-1 + NAA 0.5 mg L-1, B: spermidine 1 mmol + 2.4-D 2 mg L-1 + NAA 0.5 mg L-1, C: 2.4-D 2 mg L-1 + NAA 0.5 mg L-1. There was not polyamine influence in the calluses growth. It was observed in the treated calluses with spermidine larger cellular putrescine concentration (582.37 μg g mf-1) at 60 days, larger spermidine concentration (502.54 μg g mf-1) and spermine (868.53 μg g mf-1) at 40 days of cultivation, when the own polyamine was applied. It was concluded that the exogenous polyamine application in Hancornia speciosa does not provide an increase in the calluses growth. The oxidation promoted by long periods of in vitro cultivation induces an increase in the putrescine levels.